The Practical Analysis Of Translations From French Texts Into Uzbek - Khayatova Nigina Ikromjonovna; Nematullayeva Gulnoza Navròz qizi (Open Academia, 2025)
This article presents a practical analysis of translations of French literary texts into Uzbek, while discussing methods for adequately expressing lexical units. It examines the main challenges and strategies for conveying cultural realities, linguistic nuances, and the style of the original text. Examples from actual translations are provided with commentary. Particular attention is given to the concept of interlingual equivalence and its significance in text translation. The Uzbek and French languages belong to different language families, which leads to lexical, grammatical, and syntactic differences that pose additional challenges for translators. This is especially true for the translation of phraseological units, idioms, and culturally loaded lexemes, for which finding appropriate equivalents is crucial. In this context, the translator acts not only as a linguist but also as a cultural expert. This work provides a significant theoretical and practical framework for further scientific research and translation practices, as well as offering useful advice for translators. It emphasizes that overcoming the challenges of text translation and ensuring high quality requires a scientific approach, an understanding of cultural contexts, and linguistic competence.
Keywords: translation; lexical units; French language; linguoculturology